(untitled) (International Journal of Physiotherapy, 2022)
Background: Falls are a significant concern for people post-stroke. Interventions that effectively prevent or reduce the number of falls should be well documented and appraised for effectiveness. Therefore, our study aimed to identify and appraise the literature on interventions aimed at preventing or reducing falls among people post-stroke. Methods: A comprehensive literature search was conducted in five databases. Two independent reviewers screened the literature search results to include relevant studies. Subsequently, reviewers extracted the data using a standardized form, and the quality of studies was assessed using a critical appraisal tool. Results: 26 studies met the selection criteria and were included in our review. We identified eight categories for preventing and reducing falls. These categories were: electrotherapy, multifactorial fall prevention programs, educational programs, multifaceted stroke telerehabilitation, virtual reality, vitamin-D supplements, rehabilitation instruments, and physical activities. Conclusion: The evidence for these interventions varied between studies, with no single intervention superior to others. The current review findings indicate that there is limited evidence to recommend one fall intervention to be generalized among people post-stroke. Further studies involving large sample sizes and different fall outcomes are needed to make valuable recommendations for clinical practice.